The Triglav glacier between 1986 and 1998 - Gabrovec, Matej (Geografski zbornik, 1998)
Results are presented of thirteen-year observations of the Triglav glacier. Snow conditions in the annual accumulation period and the published results of annual measurements at the end of the melting period are described. Due to the continual thinning of the ice in the last decade, we no longer speak only of shrinking but of the disintegration of the glacier. Its surface area, which was fifteen hectares in 1946, had shrunk to less than three hectares by 1998.
Keywords: climatology; fizična geografija; Julian Alps; Julijske Alpe; klimatologija; klimatske spremembe; ledeniki; physical geography; Slovenia; Slovenija; Triglavski ledenik